Is accounting profession the right career choice? (A case of first year accounting students in Universiti Teknologi Mara Sarawak) / Dayangku Ruhayah Awang Bolhan ... [et al.] - Awang Bolhan, Dayangku Ruhayah; Kassim, Zalila@Azalilah; Jonathan, Lulu; Atan, Patrick (2007)
This study attempts to examine empirically the factors influencing the career choice of the first year Diploma in Accountancy students who have selected accounting as a profession. First year students at Universiti Teknologi Mara, Negeri Sarawak (UiTM) were used in this study as the introductory courses shapes their perceptions of the profession, the aptitudes and skills needed for successful careers in accounting and the nature of career opportunities in accounting. The data for this study were gathered through the use of questionnaires and interview. It was indicated that from the findings, self interest, parents' advice and friends or peers influence greatly influenced the respondents' decision in selecting accounting as a profession.